The Use of the Cryopreserved Aortic Homograft for Aortic Valve Replacement: Is It Still an Option? - Francesco Nappi; Antonio Nenna; Cristiano Spadaccio; Sanjeet Singh Avtaar Singh; Almothana Almazil; Christophe Acar (Journal of Cardiovascular Development and Disease, 2023)
The indications for cryopreserved allografts in aortic valve replacement are still debatable. We aim to identify factors influencing early and long-term durability of the aortic homograft and to define subgroups of patients with an improved long-term quality of life, survival, and freedom from structural valve degeneration (SVD). We evaluated our series of 210 patients who underwent allograft implantation with a retrospective cohort study design over a period of 20 years. Endpoints were overall mortality, cardiac mortality related to SVD, the incidence of SVD, reoperation, and a composite endpoint comprising major adverse cardiac and cerebrovascular events (MACCEs), which includes cardiac death both related and not related to SVD, subsequent aortic valve surgery, new or recurrent infection of implanted allograft, recurrent aortic regurgitation, rehospitalization for heart failure, an increase in New York Heart Association (NYHA) class of ≥1, or cerebrovascular events. The primary indication for surgery was endocarditis (48%), which was also a predisposing factor for increased cardiac mortality. Overall mortality was 32.4% with a 27% incidence of SVD and mortality associated with SVD of 13.8%. Reoperation occurred in 33.8% and MACCEs in 54.8%. Long-term NYHA functional class and echocardiographic parameters improved over time. Statistical analysis demonstrated that root replacement technique and adult age were protective factors for SVD. We found no statistically significant difference in the clinical outcomes analyzed between women of childbearing age who had children after surgery and the rest of the women. The cryopreserved allograft is still a valid option in aortic valve replacement, providing acceptable durability and clinical outcomes with optimal hemodynamic performance. SVD is influenced by the implantation technique. Women of childbearing age might have additional benefits from this procedure.